Government Expenditure and Economic Discomfort in Nigeria: An ARDL Approach - OBAYORI, JOSEPH BIDEMI (Finance & Economics Review, 2020)
Purpose: Government expenditure affects the behavior of both producers and consumers, and influence the distribution of income and wealth in the economy. But, a cursory look at government expenditure (recurrent and capital) in Nigeria over the year, showed that expenditure has been on the increase but the rate of increase has not translated into economic comfort (reduction in poverty and unemployment rates). Due to this assumption, this paper examined government expenditure and economic discomfort in Nigeria. Methods: Annual time-series data from 1990-2018 were obtained from the CBN Statistical Bulletin (various issues) and the World Bank report. The descriptive statistics, ADF unit root test, and ARDL model serves as the analytical tools. Results: Based on the empirical result, the paper concluded that government capital expenditure has a negative and significant relationship with economic discomfort. On the other hand, government recurrent expenditure is positively and insignificantly related to economic discomfort. Implications: This result implies that while the increase in capital expenditure will depress economic discomfort, an increase in the recurrent component of the expenditure will not help to reduce economic discomfort. Based on these conclusions, the paper recommended amongst others that more government capital spending should be encouraged as it plays a critical role in reducing both poverty and unemployment rates in Nigeria.